PENGARUH CAR, NPL, NIM, LDR TERHADAP TINGKAT PROFITABILITAS BANK NON DEVISA DI INDONESIA TAHUN 2005-2009 - Edo Pratama, 08.05.51.0068; Farchan, Farchan (Students Journal of Economic and Management, 2012)
This study aims to analyze the influence of variable capital adequacy ratio (CAR), net interest margin (NIM), non performing loans (NPL) and loan to deposit ratio (LDR) to profirabilitas. Testing the hypothesis in this study using multiple regression analysis (Multiple Regression) Samples used in this study as many as 16 non-bank foreign exchange banking institution with a purposive sampling technique, which is a technique based on the criteria for the determination of the sample. Criteria are banks that submit financial statements in 2005 until 2009. data collection techniques were tested using OLS regression method. The results after a partial test of the hypothesis shows that the CAR, NPL and the LDR is shown to have a negative effect but not significant. NIM is shown to have a positive effect on profitability but significant. NIM thus able to increase profitability. Keywords: Capital Adequacy Ratio (CAR), non-performing loans (NPLs), Net Interest Margin (NIM), and the Loan to Deposit Ratio (LDR), profitability (ROA)